Anisotropic Saturable and Excited‐State Absorption in Bulk ReS2. Issue 14 (9th May 2018) - Meng, Xianghai; Zhou, Yongjian; Chen, Ke; Roberts, Richard H.; Wu, Wenzhi; Lin, Jung‐Fu; Chen, Ray T.; Xu, Xiaochuan; Wang, Yaguo
Abstract: The intensity‐scan (I‐scan) technique to study the polarization‐dependent, nonlinear processes in exfoliated bulk ReS2 is utilized. The polarization‐dependent reflection and transmission of ReS2, from which the absorption coefficients are extracted using the transfer matrix method, are measured. Absorption coefficients under high laser peak power show a transition from saturable absorption (SA) to reverse saturable absorption when rotating the laser polarization with respect to the b ‐axis. It is found that SA and excited‐state absorption (ESA) contribute to the nonlinear optical processes. Both the SA and ESA show strong dependence on the polarization angle, which is attributed to the anisotropic optical transition probability and electronic band structure in ReS2 . The anisotropic nonlinear optical properties of ReS2 may find applications as saturable absorbers in lasers and optical modulators. Abstract : The polarization‐dependent nonlinear optical response of ReS2 is investigated through intensity‐scan technique. By controlling the laser polarization with respect to b ‐axis, a saturable absorption to reverse saturable absorption crossover is observed due to the anisotropic optical transition probability and electronic band structure, which makes ReS2 a promising material in optical applications.